Calcium carbonate mineralization in chiral mesomorphic order-retaining ethyl cellulose/poly(acrylic acid) composite films. (14th March 2018) - Katsumura, Ayaka; Sugimura, Kazuki; Nishio, Yoshiyuki
Abstract: A CaCO3 mineralization was carried out using a mesomorphic network system composed of ethyl cellulose (EC) and poly(acrylic acid) (PAA), to realize a polymer–inorganic hybrid invested with a chiroptical functionality and thermal and mechanical high-performances. The EC/PAA samples were prepared in colored film form from chiral nematic liquid crystals of EC in acrylic acid (AA) by polymerization and cross-linking of the solvent monomer AA. The mineralization was allowed to proceed in a batchwise operation by immersing and swelling the liquid-crystalline polymer films in an aqueous salt solution providing Ca 2+, HCO3 −, and additional Mg 2+ ions. By varying the ionic condition (i.e., pH and Mg/Ca ratio) of the employed salt solution, calcite (Cal), aragonite (Ara), and solely amorphous CaCO3 (ACC) were separately deposited inside the EC/PAA matrices. Irrespective of the polymorphs of the incorporated CaCO3, the mineralized EC/PAA films (weight gain, ca. 20–28%) retained the original left-handed chiral nematic arrangement and exhibited a reflective color that was shifted to the red side relative to that of the corresponding nonmineralized films. It was also confirmed that the inorganic hybridization remarkably enhanced the thermal and thermomechanical properties of the optically functionalized EC/PAA films. In thermogravimetric analysis data above 300 °C, however, a significant difference was observed between the three sorts of hybrids with Cal, Ara, and ACC, respectively. Graphical abstract: Highlights: CaCO3 mineralization was conducted using a chiral mesomorphic EC/PAA network. Calcite, aragonite, and amorphous CaCO3 were separately deposited inside the matrix. The resulting hybrids imparted cholesteric colorations as a chioptical characteristic. The mineralized films were improved in heat-resistance and mechanical performance.